Multicompartmental Lipopolyplex as Vehicle for Antigens and Genes Delivery in Vaccine Formulations - Isaías Sanmartín; Luis Sendra; Inés Moret; María José Herrero; Salvador F. Aliño (MDPI AG, 2021)
Vector design and its characterization is an area of great interest in current vaccine research. In this article, we have formulated and characterized a multicompartmental lipopolyplex, which associates multiple liposomes and polyplexes in the same complex. These particles allow the simultaneous delivery of lipid or water-soluble antigens associated with genes to the same cell, in much higher amounts than conventional lipopolyplexes. The vector characterization and optimization were carried out using liposomes with entrapped carboxyfluorescein and adapted electrophoretic assays. Two types of lipopolyplexes (containing hydrophilic or lipophilic antigens) were employed to evaluate their interest in vaccination. The lipopolyplex loaded with an extract of water-soluble melanoma proteins proved to efficiently induce humoral response in murine melanoma model, increasing the levels of IgM and IgG. The specificity of the immune response induced by the lipopolyplex was demonstrated in mice with the lipopolyplex containing the GD3 ganglioside lipid antigen, abundant in melanoma cells. The levels of anti-GD3 IgG increased markedly without modifying the expression of humoral antibodies against other gangliosides.